Ecdysone regulates morphogenesis and function of malpighian tubules in Drosophila melanogaster through EcR-B2 isoform. - Gautam, N.K.; Verma, P.; Tapadia, M.G. (Developmental Biology, 2015)
Malpighian tubules are the osmoregulatory and detoxifying organs of Drosophila and its proper development is critical for the survival of the organism. They are made up of two major cell types, the ectodermal principal cells and mesodermal stellate cells. The principal and stellate cells are structurally and physiologically distinct from each other, but coordinate together for production of isotonic fluid. Proper integration of these cells during the course of development is an important pre-requisite for the proper functioning of the tubules. We have conclusively determined an essential role of ecdysone hormone in the development and function of Malpighian tubules. Disruption of ecdysone signaling interferes with the organization of principal and stellate cells resulting in malformed tubules and early larval lethality. Abnormalities include reduction in the number of cells and the clustering of cells rather than their arrangement in characteristic wild type pattern. Organization of F-actin and ?-tubulin also show aberrant distribution pattern. Malformed tubules show reduced uric acid deposition and altered expression of Na(+)/K(+)-ATPase pump. B2 isoform of ecdysone receptor is critical for the development of Malpighian tubules and is expressed from early stages of its development.